Gene Therapy and Its Application in Breast Cancer Treatment - Sheng, Sifei (Transactions on Materials, Biotechnology and Life Sciences, 2024)
As a new medical field, gene therapy has shown great potential in cancer treatment. This article reviews the principle, mechanism and application of gene therapy in the treatment of breast cancer, and discusses the prospect and challenge of its future development. Mutation, as the common cause of cancer, is the target of gene therapy. By replacing disease-causing genes, suppressing malfunctioning genes, or introducing new genes, a variety of mutation caused disease could be treated... In particular, this paper presents genome editing technologies such as CRISPR-Cas9, which correct genetic differences by precisely modifying existing DNA within cells. Finally, this paper discusses the future development of gene therapy, including its application in multiple cancer models, and the safety challenges faced. Despite some serious problems, such as immune responses and non-specific targeting, the potential of gene therapy is still huge. As technology continues to advance, we expect gene therapy to revolutionize cancer treatment.